Changes in the relative situation of the poor in a growing economy – the case of Poland - Kośny, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The permanently positive economic growth in Poland over the last twenty years has resulted in a significant improvement in the economic situation of households. The distribution of this increase in wealth was not, however, homogenous, and the pattern of income growth proved to be a crucial factor determining the situation of the poor. The aim of the paper is to investigate to what extent the characteristics of the households influence the income growth pattern. Three main groups of households will be considered: the selfemployed and blue- and white-collar workers. The analysis is based on the relative concept of changes in income distribution. Besides the commonly known income growth curves, diagrams related to the Zenga inequality index will be applied.
Mathematical Economics, 2012, Nr 8 (15), s. 83-96
Keywords: economic growth; pro-poor growth; poverty; income distribution